2018
DOI: 10.1002/2017ja024411
|View full text |Cite
|
Sign up to set email alerts
|

A Year‐Long Comparison of GPS TEC and Global Ionosphere‐Thermosphere Models

Abstract: The prevalence of GPS total electron content (TEC) observations has provided an opportunity for extensive global ionosphere‐thermosphere model validation efforts. This study presents a year‐long data‐model comparison using the Global Ionosphere‐Thermosphere Model (GITM) and the Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model (TIE‐GCM). For the entire year of 2010, each model was run and compared to GPS TEC observations. The results were binned according to season, latitude, local time, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…Perlongo et al (2018) showed that this is partly related to a very large O∕N 2 ratio, in particular at low latitudes. First, it appears that the heating mechanisms in GITM might be too strong compared to the cooling mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Perlongo et al (2018) showed that this is partly related to a very large O∕N 2 ratio, in particular at low latitudes. First, it appears that the heating mechanisms in GITM might be too strong compared to the cooling mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…In most cases, 11_CTIPE and 6_GITM tend to underestimate percentage changes, while 1_UAM‐P and 11_TIE‐GCM overestimate them. The differences in performance among these four simulations could be caused by inherent differences among the models, for example, different methods to solve for chemistry and advection, and different ways to treat eddy diffusion and vertical transport (Fuller‐Rowell et al, ; Perlongo et al, ; Prokhorov et al, ; Ridley et al, ; Solomon et al, ). In addition, the performance differences could also be caused by a combination of different input data and different models used for lower boundary forcing and high‐latitude electrodynamics, since each simulation was obtained by using its default input data and drivers.…”
Section: Discussionmentioning
confidence: 99%
“…The Ionosphere Plasmasphere Density Working Team performed its first validation study of foF2 and TEC predictions using various ionosphere/thermosphere models. This study is the first quantitative assessment of both parameters based on a set of metrics, unlike a number of validation studies done previously (Anderson et al, ; Araujo‐Pradere et al, ; Burns et al, ; Feltens et al, ; Fuller‐Rowell, Codrescu, et al, ; Orús et al, , ; Perlongo et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…We would expect the correction of N 2 and other parameters in the lower thermosphere to bring the model results even closer to the observations. It was shown by Perlongo et al (2018) that GITM has lower summer electron densities than the GPS TEC observations in both the northern and southern midlatitudes. Using GITM w/ WACCM-X at the lower boundary, this will potentially be corrected as the electron density depends on the O/N 2 .…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 93%